2012
DOI: 10.3390/ijms131113781
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of Coronary Arteriolar Endothelium-Dependent Dilation after Multi-Walled Carbon Nanotube Inhalation: A Time-Course Study

Abstract: Engineered nanomaterials have been developed for widespread applications due to many highly unique and desirable characteristics. The purpose of this study was to assess pulmonary inflammation and subepicardial arteriolar reactivity in response to multi-walled carbon nanotube (MWCNT) inhalation and evaluate the time course of vascular alterations. Rats were exposed to MWCNT aerosols producing pulmonary deposition. Pulmonary inflammation via bronchoalveolar lavage and MWCNT translocation from the lungs to syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
96
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(104 citation statements)
references
References 60 publications
(79 reference statements)
7
96
0
Order By: Relevance
“…We have previously observed this type of dysfunction after pulmonary exposure to nanomaterials such as titanium dioxide (Nurkiewicz et al , 2011; Stapleton et al , 2015), cerium dioxide (Minarchick et al , 2013; Minarchick et al , 2015), and carbon nanotubes (Stapleton et al , 2012). However, single toxicant based studies do not accurately relate to the complexity of emissions generated by the 3D printing process.…”
Section: Discussionmentioning
confidence: 86%
“…We have previously observed this type of dysfunction after pulmonary exposure to nanomaterials such as titanium dioxide (Nurkiewicz et al , 2011; Stapleton et al , 2015), cerium dioxide (Minarchick et al , 2013; Minarchick et al , 2015), and carbon nanotubes (Stapleton et al , 2012). However, single toxicant based studies do not accurately relate to the complexity of emissions generated by the 3D printing process.…”
Section: Discussionmentioning
confidence: 86%
“…These drugs were evaluated in patients with an underlying pulmonary disease (e.g., asthma and chronic obstructive pulmonary disease) and the data presented indicate that the drugs can be used upon exacerbation of the pulmonary disease; however, intense and thorough evaluation of the glucose (in the case of diabetes) has to be performed since the pharmacokinetics of the administered drug are altered. Our work provides, for the first time, the proof of concept that aerosolized chemotherapy is distributed efficiently in lymph node tissue in early-stage lung cancer patients and, therefore, it can be used as a neoadjuvant and/or adjuvant treatment [33]. Acknowledgements P Zarogoulidis would like to thank C Ritzoulis, Technical Institute of Food Administration and Aristotle University of Thessaloniki, for his technical assistance in measuring the aerosol droplets with the Mastersizer 2000 laser scattering apparatus (Malvern Instruments, Worcestershire, UK).…”
Section: Future Science Groupmentioning
confidence: 96%
“…Oxidative stress is considered to be an important mechanism of action for carbon nanotube-mediated health effects (Shvedova et al, 2012). Airway exposure to MWCNTs in animals have shown impairment of endothelium-dependent vasodilation in coronary arteries (Stapleton et al, 2012), accelerated plaque progression in aorta (Cao et al, 2014), and exacerbated myocardial infarction after ischemia/reperfusion injury (Thompson et al, 2014;Urankar et al, 2012). In vitro model systems have shown that MWCNT exposure can induce the production of reactive oxygen species (ROS) and the expression of adhesion molecules in cultured endothelial cells (Cao et al, 2014;Pacurari et al, 2011;Vidanapathirana et al, 2012).…”
Section: Introductionmentioning
confidence: 99%